2013
DOI: 10.1371/journal.pone.0070834
|View full text |Cite
|
Sign up to set email alerts
|

Association of Four Genetic Polymorphisms of AGER and Its Circulating Forms with Coronary Artery Disease: A Meta-Analysis

Abstract: BackgroundConsiderable efforts have been devoted to evaluating the association of the receptor for advanced glycation end-products (gene AGER and protein: RAGE) genetic variants to coronary artery disease (CAD); the results, however, are often irreproducible. To generate more information, we sought to explore four common polymorphisms of AGER and its circulating forms associated with the risk of CAD via a meta-analysis.Methodology/Principal FindingsArticles were identified by searching PubMed, EMBASE, Wanfang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Our results demonstrating the lack of a significant effect of AGER variation on cardiovascular outcomes in whites are consistent with most prior case-control studies [ 29 , 30 ] and extend these findings using a prospective cohort design which addresses confounding and selection bias more fully. While some case-control studies have identified associations between AGER SNPs and myocardial infarction and stroke [ 31 ] and prevalent coronary heart disease based on angiographic evidence of stenosis >50% [ 32 ], two recent meta-analyses including over 25 case-control studies (maximum N for single SNP = 7,111) [ 29 ] did not find a consistent association between AGER polymorphisms and coronary heart disease (odds ratios from meta-analyses ranged from 0.97 to 1.16 with P >0.05) [ 29 , 30 ]. It is important to note, however, that rs2070600 has been associated with other diseases, including type 1 diabetes [ 33 ], chronic obstructive pulmonary disease [ 26 ], schizophrenia [ 34 ], and Alzheimer’s Disease [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrating the lack of a significant effect of AGER variation on cardiovascular outcomes in whites are consistent with most prior case-control studies [ 29 , 30 ] and extend these findings using a prospective cohort design which addresses confounding and selection bias more fully. While some case-control studies have identified associations between AGER SNPs and myocardial infarction and stroke [ 31 ] and prevalent coronary heart disease based on angiographic evidence of stenosis >50% [ 32 ], two recent meta-analyses including over 25 case-control studies (maximum N for single SNP = 7,111) [ 29 ] did not find a consistent association between AGER polymorphisms and coronary heart disease (odds ratios from meta-analyses ranged from 0.97 to 1.16 with P >0.05) [ 29 , 30 ]. It is important to note, however, that rs2070600 has been associated with other diseases, including type 1 diabetes [ 33 ], chronic obstructive pulmonary disease [ 26 ], schizophrenia [ 34 ], and Alzheimer’s Disease [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…There has been extensive research on sRAGE and esRAGE in patients with type 2 diabetes, and lower levels of both sRAGE and esRAGE may be markers of poor glycemic control [ 56 ] and of increased risk of microvascular complications [ 57 ]. However, whether elevated sRAGE is associated with a higher or lower risk of cardiovascular risk during diabetes remains controversial [ 53 , 56 ], and contradictory findings from previous studies may be explained by rather small sample sizes that may have hampered the detection of clinically relevant effect sizes [ 58 ]. In addition, studies of RAGE isoforms in health and diseases should also ideally integrate the roles of ethnicity [ 59 ] and of RAGE gene variants [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several relevant meta-analyses have analyzed the relationship between the Gly82Ser polymorphism and CAD susceptibility, [42,43] there are some differences. More eligible studies were included in our study and 5 genetic models gave us a comprehensive understanding of the relationship between the Gly82Ser polymorphism and susceptibility to CAD.…”
Section: Discussionmentioning
confidence: 99%